ANALYSIS OF NONMAGNETIC METAL INDUCTION HEATING PROCESSES BY FLAT-TYPE CIRCULAR SOLENOIDAL FIELD - Batygin, Yu.; Chaplygin, E.; Barbashova, M.; Shinderuk, S.; Gavrilova, T.; Батыгин, Ю. В.; Чаплыгин, Е. А.; Барбашова, М. В.; Шиндерук, С. А.; Гаврилова, Т. В.; Батигін, Ю. В.; Чаплигін, Є. О.; et al. (Харьковский национальный автомобильно-дорожный университет, 2016)
The article analyzes the electromagnetic processes in the system of induction heating with estimating the main characteristics of heating the non-magnetic sheet metal. The analytical expressions for numerical estimates of the induced current in terms of the phase of the excitation signal are presented. The dependence for the heating temperature of the considered circular sheet metal area for the time corresponding to the interval phase has been determined.
АНАЛИЗ ПРОЦЕССОВ ИНДУКЦИОННОГО НАГРЕВА НЕМАГНИТНЫХ МЕТАЛЛОВ ПОЛЕМ ПЛОСКОГО КРУГОВОГО СОЛЕНОИДА
АНАЛІЗ ПРОЦЕСІВ ІНДУКЦІЙНОГО НАГРІВАННЯ НЕМАГНІТНИХ МЕТАЛІВ ПОЛЕМ ПЛОСКОГО КРУГОВОГО СОЛЕНОЇДА
Keywords: induction heating; induction system; induced current; electromagnetic processes; eddy currents; metal heating; temperature dependence; индукционный нагрев; индукторная система; вихревые токи; індукційне нагрівання; індукторна система; вихрові струми; 621.318.4